Comparison of batch and continuous operation modes for maxilon red azo dye removal using Chlorella vulgaris microalgae within photobioreactor (PBR) and a dynamic membrane photobioreactor (DMPBR) - Farastoon Dashti, Shaghayegh Sadat; Ansari, Iman; Emamshoushtari, Mir Mehrshad; Helchi, Salar; Lesage, Geoffroy; Heran, Marc; Pajoum Shariati, Farshid (Frontiers in Membrane Science and Technology, 2025)
This study aimed to contrast the effectiveness of Chlorella vulgaris microalgae in decolorizing Maxilon Red, an azo-red dye typically found in textile wastewater. It contrasted the dye removal efficiency of two photobioreactor models, a conventional photobioreactor (PBR) and a dynamic membrane photobioreactor (DMPBR). Batch mode operation was used for the PBR, while the DMPBR was carried out continuously. The initial concentration of dye ranged from 5 to 30 mg L−1. Kinetic analysis was used to check the model that gave the best correlation, and isotherm studies were carried out to explain the adsorption mechanism. Fourier-transform infrared spectroscopy (FTIR) was used to identify functional groups involved in binding with the dye. In the PBR, dye removal efficiency increased from 73% to 86% with a rise in initial dye concentration from 5 to 15 mg L−1, but decreased to 53% at 30 mg L−1 due to saturation phenomena. The Elovich model best represented the adsorption kinetics, indicating a heterogeneous surface and decreasing adsorption rate with time. Isotherm data also conformed to the Langmuir model, suggesting monolayer adsorption with a maximum of 8.16 mg g−1 capacity. FTIR confirmed the involvement of hydroxyl, carbonyl, and polysaccharide groups in dye binding. DMPBR, operated in continuous mode, achieved greater and constant removal efficiency of approximately 98% at 15 mg L−1 due to prolonged and uninterrupted contact between dye and biomass. The continuous DMPBR configuration overcame batch PBR saturation limitations, with enhanced biosorption activity, process stability, and improved effluent quality. Overall, the DMPBR was more efficient and sustainable in azo dye removal from wastewater than the traditional PBR.